Age and the amplitude of accommodation measured using dynamic retinoscopy. (9th September 2015) - León, Alejandro; Estrada, Jorge M.; Rosenfield, Mark
Abstract: Purpose: Dynamic retinoscopy (DR) is a procedure for assessing the accommodative response using a standard clinical instrument. The present study compared measurements of the amplitude of accommodation (AA) obtained using this technique with two subjective methods (modified push‐down and minus lens). Additionally, the expected ranges for AA when measured by DR were determined. Method: AA was measured in 1298 subjects between 5 and 60 years of age using the three techniques described above. Subjects were grouped into 5‐year bins, and a descriptive univariate analysis of the data performed. Goodness‐of fit plots were constructed to examine the overall model fit. Centile curves were calculated from the final model. Results: Mean values of AA obtained using DR were significantly lower than for the two subjective techniques. For the DR findings, no significant change was observed between 5 and 19 years of age (mean AA = 8.3 D) and between 45 and 60 years of age (mean AA = 0.6 D). AA values as a function of age were best fit by the polynomial regression equation: logAA = 1.93 + 0.49(age) − 0.19(age) 2 . Conclusion: Measurements of AA determined using DR are significantly lower than the normative subjective findings published previously. This difference is at least partly due to the depth‐of‐field of the eye. These norms markedly overestimate accommodative responsivity. DR provides a simple technique for quantifying accommodation in the clinical setting.